If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10i = 8 + -1(4iy) Reorder the terms: -10i + 2x = 8 + -1(4iy) Remove parenthesis around (4iy) -10i + 2x = 8 + -1 * 4iy Multiply -1 * 4 -10i + 2x = 8 + -4iy Solving -10i + 2x = 8 + -4iy Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '4iy' to each side of the equation. -10i + 4iy + 2x = 8 + -4iy + 4iy Combine like terms: -4iy + 4iy = 0 -10i + 4iy + 2x = 8 + 0 -10i + 4iy + 2x = 8 Add '-2x' to each side of the equation. -10i + 4iy + 2x + -2x = 8 + -2x Combine like terms: 2x + -2x = 0 -10i + 4iy + 0 = 8 + -2x -10i + 4iy = 8 + -2x Reorder the terms: -8 + -10i + 4iy + 2x = 8 + -2x + -8 + 2x Reorder the terms: -8 + -10i + 4iy + 2x = 8 + -8 + -2x + 2x Combine like terms: 8 + -8 = 0 -8 + -10i + 4iy + 2x = 0 + -2x + 2x -8 + -10i + 4iy + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 -8 + -10i + 4iy + 2x = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-4 + -5i + 2iy + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-4 + -5i + 2iy + x)' equal to zero and attempt to solve: Simplifying -4 + -5i + 2iy + x = 0 Solving -4 + -5i + 2iy + x = 0 Move all terms containing i to the left, all other terms to the right. Add '4' to each side of the equation. -4 + -5i + 2iy + 4 + x = 0 + 4 Reorder the terms: -4 + 4 + -5i + 2iy + x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -5i + 2iy + x = 0 + 4 -5i + 2iy + x = 0 + 4 Combine like terms: 0 + 4 = 4 -5i + 2iy + x = 4 Add '-1x' to each side of the equation. -5i + 2iy + x + -1x = 4 + -1x Combine like terms: x + -1x = 0 -5i + 2iy + 0 = 4 + -1x -5i + 2iy = 4 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4-C=25 | | 8X+8=5X+7 | | 9*x*x*x+6*x*x=0 | | 15+4y=y | | 125-3x=24+23x | | 2x-10i=8-(4y)I | | 27-18=3(X-3) | | 12-8x=123-43x | | -127-8x=-68-10x | | 28+3Y-6=13Y-13-3Y | | 5x+3=27-4x | | 6x+21=5x-51 | | x+19+3x=-15-3x-22 | | 114-6x=9+24 | | 5x+2y-3x+4y= | | 4x+34=5x+1 | | 8x^3-8x^2+x=4x^2-5x+1 | | 3x-7=7x-17 | | 18.23=x+0.21*x | | 7x+13=97-6x | | 75-5x=8x+18 | | 11x-5x+1=-65x+36 | | 3(2x-3)-(4x-5)=0 | | 3x-11=75-5x | | 2x-3=7(x-2)4 | | 3*3-3*3=2 | | 5-5=5X+4X | | 5*9+5*4=280 | | 10W-17W=-49 | | -3-5=-6+X | | 3x(2)+7=5(3x+4) | | 3x+4*5=6 |